SUNSERUM WAJAH SARI RIMPANG TEMU GIRING (Curcuma heyneana) TERFERMENTASI Lactobacillus bulgaricus - Andriani, Irma; Mardianingrum, Richa; Susanti (Universitas Imelda Medan, 2023)
Long-term sun exposure can cause a variety of skin disorders, including sunburn and skin cancer. Sunscreen products containing antioxidants can help to prevent unwanted effects and protect the skin from free radicals. The rhizome of sleigh meeting (Curcuma heyneana) has chemicals 1,4- napthalenedione, 2-hydroxy-3-(-2-methyl-prophenyl), or other names Norlapachol, which has the potential as a suya screen and has strong antioxidant action. The study's goal is to see if the juice of fermented rhizome of Lactobacillus bulgaricus can be created as a sun serum face preparation, and then compare the value of antioxidant activity and sunscreen. Making fresh juice, fermented juice, phytochemical screening, preparation making, preparation evaluation, and SPF test are all part of the procedure. creating fresh juice, fermented juice, phytochemical screening, creating preparations, evaluating preparations, in-vitro SPF testing using a UV-Vis spectrophotometer, and antioxidant testing with the DPPH (2,2-Dyphenyl-1- Pycrylhydrazyl) method are all part of the approach. SPF F1 test value: 27.40 (ultra protected); F2: 27.84 (ultra protected); antioxidant activity test results: the IC50 value of fresh juice is 15.92 ppm (very strong); fermented juice is 11.02 ppm (very strong); and all preparation evaluations met the requirements according to the test standards. According to the findings, fresh and fermented ginger rhizome juice can be prepared as a sunscreen and antioxidant-rich facial sun serum preparation.